Factors that Influence Counterproductive Behavior at Gatot Soebroto Presidential Hospital - Dumonda, Vera; Saptono, Ari; Suparno, Suparno (AIBPM Publisher, 2023)
The purpose of this research is to identify the elements that influence counterproductive based on the variables of communication skills and competence at the Gatot Subroto Presidential Hospital. This is a quantitative study. The sample in this study consisted of 1580 voluntary employees, 1250 employees of the Gatot Soebroto Army Hospital, 330 employees of the YMU Pavilion, and 1136 nursing staff. The sampling technique used is probability sampling, namely random sampling. This is a survey method that employs path analysis. The study's findings revealed a good and significant direct relationship between communication skills and competency. There is a direct effect that is negative but not significant between communication skills and counterproductive behavior. However, there is a substantial relationship between communication skills on counterproductive behavior through competence. Finally, there is a considerable detrimental influence between competence on counterproductive behavior. Based on the results, it can be concluded that counterproductive behavior is influenced by communication skills through competence. Therefore, it is hoped that the Gatot Soebroto Army Central Hospital can improve communication skills and competencies to reduce counterproductive behavior in health workers working at the Gatot Soebroto Army Central Hospital.